Bending behavior of cement-based multi-layered roof elements. (1st July 2019) - Zani, Giulio; Rampini, Marco Carlo; Colombo, Matteo; di Prisco, Marco
Highlights: Innovative cementitious materials can be employed in lightweight structures. Lighter roof solutions can indirectly secure existing frames and foundations. Cement-based sandwich elements offer remarkable strength, ductility and robustness. Preliminary attempt of technological transfer of HPFRCC from the lab to the precast plant demands attention. Abstract: The two major earthquakes occurred in Northern Italy in 2012 (magnitude 6.1 and 5.8) shown that a serious debate over the structural safety of existing industrial buildings is utterly necessary, also in regions traditionally considered less exposed to the seismic hazard. A promising retrofitting strategy may be represented by the substitution of inefficient secondary roof components with innovative lightweight panels, capable of simultaneously ensuring a global reduction of the inertial forces and an increase of the building energy performances. In this paper, the structural behavior of a multilayered solution, consisting of an advanced cement-based case enclosing a thick insulating core, is presented and investigated on real-scale specimens. The mechanical characterization of the employed materials (High-Performance Fiber Reinforced Cementitious Composite and Textile Reinforced Concrete) at the laboratory level is followed by the discussion of the major challenges arisen in transferring such sensitive construction technologies to the prototyping plant. Structural performances are evaluated by means of longitudinal and transverse bending tests and simplified plane-section design approaches are finally explored and critically assessed.